PENGARUH PENERAPAN SISTEM INFORMASI AKUTANSI TERHADAP KINERJA KARYAWAN BRI CABANG BANDA ACEH - Dico Wiranto; Muslim Muslim (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The problem in this study is whether How Accounting Information Systems affect Employee Performance. The purpose of this study was to determine the effect of the effect of Accounting Information Systems on Employee Performance. The location of the study is at PT Bank BRI Banda Aceh, the number of respondents is 105 customers, while  the  sampling  technique  uses  Non  Probability  Sampling  where  researchers  accidentally  meet  with  the Employee, the technique of collecting data is a questionnaire, data analysis is calculated with the help of SPSS 19.0 with qualitative analysis tools and quantitatively and using a simple regression analysis hypothesis test. From the results of the research and discussion of the analysis of the results that have been carried out in this study, it can be concluded that the Accounting Information System has a positive effect on Employee Performance at the BRI Branch and the Banda Aceh Region. It can be said that accounting information systems are very helpful for a number of employee jobs, and SIA at Bank BRI is currently quite good at measuring performance. It has been proven in this study that AIS assesses that employee performance can be assessed from a program